MS EXCEL ПРОГРАММАСЫ ЖӘРДЕМИНДЕ ТРАНСПОРТ МӘСЕЛЕСИН ПОТЕНЦИАЛЛАР УСЫЛЫ МЕНЕН ШЕШИЎ - Жалелов, Р.М.; Жалелов, K.М. (FAN va JAMIYAT, 2020)
The article deals with a role of a transport problem of linear programming in the field of economy. It is considered the decision of this problem by a method of potentials by means of program MS Excel.